Influence of Service Quality on Student Satisfaction in Online Learning at the Polines Business Administration Department - Riyanto, Makmun -; Taviyastuti, Taviyastuti -; Suroija, Noor -; Zaenuddin, Achmad - (Politeknik Negeri Semarang, 2023)
Online learning is a solution that is widely used in Indonesia during the Covid 19 pandemic at all levels/levels of education. Online learning is the main method chosen so that the learning process continues and the transfer of knowledge from teachers to students continues. Even though the application facilities used have varied, it does not mean that all learning processes are going well and satisfying students. Therefore, this research was conducted to find out whether the quality of online learning services in Business Administration majors has satisfied students. This is important to know as an effort to evaluate and improve if there is something that needs to be fixed and also if in the future an online learning process is carried out again. The results of quantitative analysis based on the regression value of each variable shows a positive effect. The first has the greatest influence on student satisfaction is the Empathy variable (X6) which is equal to 0.691, then the Assurance variable (X5) is 0.643, the Ease of use variable (X2) is 0.372, the Responsiveness variable (X4) is 0.340, the Responsiveness variable (X3) is 0.270, and the last is the Website design variable (X1) of 0.047. However, based on the t test, there were only 3 variables that had a significant effect on student satisfaction in online learning during the Covid 19 pandemic, namely the Ease of use variable (X2), the Assurance variable (X5), and the Empathy variable (X6). Judging from the Adjusted R2 value, it is obtained a number of 0.610, which means 61% of the variance of student satisfaction in online learning for the Business Administration Department is explained by the variance of the variables Website design, Easy of use, Reliability, Responsiveness, Assurance, and Empathy, while the rest (100% - 61% = 39%) is explained/influenced by other factors not examined in this study